Pemanfaatan Material Baja X-Ses Di Kota Cilegon Sebagai Material Bilah Golok Banten - Deprilen Dacha; Iman Saefullah; Haryadi Haryadi (Politeknik Negeri Padang, 2020)
Sulangkar machetes is one of the typical Banten machetes that have strong cultural values. Sulangkar means “sulang” and “sekar” which means stacked with two different materials. The lack of raw materials is a problem in the process of making sulangkar machetes. In this study, the combination of SS400 Steel and Leaf Spring Steel was observed for its mechanical properties as the raw material for Sulangkar machetes. In this study, Sulangkar machetes material consists of three layers of material, two layers of SS400 steel and leaf-spring steel inserted in the middle. The three-layers material are forged after being heated to a temperature of 750°C in a furnace. The material that has been forged then tested for tensile strength, toughness and hardness. The results of the tensile test showed that the leaf spring steel has the highest strength value of 1324.52 Mpa. The results of the Impact test show that the SS400 material has the highest Impact value of 163 J. The hardness test results show that the combination material has the highest hard value of 716.89 HBW.